Analisis Struktur Perekonomian Bali: Pendekatan Shift Share - Hani Putri, Christina; Rustariyuni, Surya Dewi (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 1, No. 2, Desember 2012, 2012)
The purpose of this study was to analyze the structure of the local economy and shifting views of the nineth sector employment and contribution to GDP of Bali Province in 2000-2011. Location of the research conducted in the province of Bali used to analysis techniques shift share approach. The results indicate a change of shift share structure of the economy in the province of Bali in 2000-2011. Shifting views nineth sector of employment shows the agricultural sector has the lowest value of -26.44 percent, PHR has the highest value of 45.18 percent. Contribution to GDP indicates the agricultural sector has the lowest value of 14.72, PHR sector has the highest value of 35.41 percent.
Keywords: labor absorption shift , economic structure , shift share